Extranodal NK/T-cell lymphoma: a review of literature and case report - N. G. Chernova; M. V. Nareyko; M. N. Sinitsyna; Yu. V. Sidorova; G. A. Yatsy; A. M. Kovrigina; E. E. Zvonkov; V. N. Dvirnyk; L. A. Kuz’mina; E. N. Parovichnikova; V. G. Savchenko (Онкогематология)
Extranodal NK/T-cell lymphoma – a rare lymphoproliferative disease characterized predominantly by extranodal localization, aggressive course and low efficiency of conventional chemotherapy. Clinical presentation is diverse and depends on tumor lesion localization. In this article, a literature review and case report of patient with generalized extranodal NK/T-cell lymphoma with bone marrow involvement, unusual intracranial tumor localization, tumor leukemization and central nervous system-leukemia were presented. Adequate treatment strategy made it possible to achieve long-term complete remission in a patient with poor prognosis.